Application of project-based change management in construction: a case study - Chen, Chun-Sung; Tsui, Yu-Kun; Dzeng, Ren-Jye; Wang, Wei-Chih (Journal of Civil Engineering and Management, 2014)
Real-time information is vital to enhance dynamic control and management via information sharing and analysis in order to reduce construction conflicts and project delays. However, most construction project management programs are ineffective for project prompt responses, especially with respect to change management. This work presents a novel construction project management system called the web project-based change management (WPCM) system. The WPCM system responds to changes in information efficiently in order to facilitate change management among project participants (e.g. general contractor, suppliers, and subcontractors) in a construction project environment. Capable of increasing information sharing in construction change management, web-based technology can also provide cost savings via the Internet. A case study involving a commercial building project in Taiwan demonstrates the effectiveness of both the proposed WPCM system and information sharing in change control during the construction phase. In addition to increasing the efficiency of change control and management for a general contractor, as well as dynamic project tracking and management, the proposed system enables subcontractors and suppliers to access and manage the change information timely. Future work should implement the system functions comprehensively and apply the system to additional projects more strictly for further verification of its reliability.